Analisis Resepsi Followers Akun @rubicommunity Terhadap Kampanye Pemberdayaan Perempuan Di Instagram - Prasasti, Yulianti Ratih (MASSIVE: Jurnal Ilmu Komunikasi, 2024)
This research analyzes how followers of the Instagram account @rubicommunity interpret the empowerment content uploaded on the account. The followers' interpretations are examined using Stuart Hall's reception analysis and the Encoding-Decoding theory to dissect this study. The methodology employs a qualitative approach with a constructivist paradigm. Data collection techniques involve analyzing the empowerment content and conducting in-depth interviews with four informants who are followers of @rubicommunity. The findings reveal that the four informants have varying interpretations of several aspects of women's empowerment content. These differences in interpretation are influenced by personal experiences, social environment, and culture. The study demonstrates that how informants interpret women's empowerment content can influence their views on Generation Z behavior in the current era of globalization, thereby yielding diverse impacts and reflections for each informant.Keywords: Reception Analysis, Women's Empowerment, Social Media, Instagram @rubicommunity.